PROSPECTS FOR THE USE OF CRYPTOCURRENCY AND BLOCKCHAIN TECHNOLOGIES FOR BANK PLASTIC CARDS (American Journal of Business Management, Economics and Banking, 2024)
This paper explores the potential applications and prospects of utilizing cryptocurrency and blockchain technologies for bank payment cards in Uzbekistan. An analysis of the current financial landscape in Uzbekistan is conducted, examining the adoption of digital payments, mobile banking, and openness to emerging financial technologies. The core features and benefits of integrating cryptocurrency and blockchain solutions into bank card infrastructures are discussed, including enhanced security, transparency, efficiency, and financial inclusion. Key challenges and considerations for implementation are also highlighted. The paper argues that while there is significant potential for these technologies to transform the bank card space in Uzbekistan, a measured approach in partnership with regulatory bodies is needed for successful adoption. Further research and controlled pilot programs are recommended to validate use cases and inform a national strategy.